2016
DOI: 10.3109/13814788.2016.1144746
|View full text |Cite
|
Sign up to set email alerts
|

Medical students’ attitudes and wishes towards extending an educational general practice app to be suitable for practice: A cross-sectional survey from Leipzig, Germany

Abstract: Fourth year medical students from Leipzig, Germany, were interested in using a general practice app during and after medical education. The responding students anticipated using a future general practice app mainly for collaboration, access to knowledge and diagnostic purposes when working as physicians. ABSTRACTBackground: In medical education and practice, smartphone apps are increasingly becoming popular. In general practice, apps could play an important future role in supporting medical education and pract… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
8
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(8 citation statements)
references
References 24 publications
0
8
0
Order By: Relevance
“…It has been recommended that applications developed for a variety of patient cases could improve the clinical decision-making skills of dental students (Deshpande, Kalaskar & Chahande, 2016). Sandholzer et al. (2016) also revealed that using m-learning apps which are designed to support medical students’ knowledge contributes to active student learning.…”
Section: Discussionmentioning
confidence: 99%
“…It has been recommended that applications developed for a variety of patient cases could improve the clinical decision-making skills of dental students (Deshpande, Kalaskar & Chahande, 2016). Sandholzer et al. (2016) also revealed that using m-learning apps which are designed to support medical students’ knowledge contributes to active student learning.…”
Section: Discussionmentioning
confidence: 99%
“…It has been recommended that applications developed for a variety of patient cases could improve the clinical decision-making skills of dental students (Deshpande et al, 2016). Sandholzer, Deutsch, Frese, and Winter (2016) also revealed that using m-learning apps which are designed to support medical students' knowledge contributes to active student learning. The students preferred to watch videos on YouTube for educational purposes from their smartphones, a finding that was supported by a recent study where students found YouTube videos more helpful than traditional teaching methods (Khatoon et al, 2014).…”
Section: Discussionmentioning
confidence: 99%
“…Recently, the introduction of several modern learning methods, including simulations, internet-based resources, and smartphone apps (i.e., dry-based methods), has resulted in better skill set development among medical undergraduate students [ 1 – 4 ]. However, experimental activities (i.e., wet-based methods) have also been proven to induce effective understanding of physiological educational content through their interactive approaches [ 1 , 5 , 6 ].…”
Section: Introductionmentioning
confidence: 99%